Parents’ Perceptions of Teachers’ Authority and Parental Involvement: The Impact of Communality - Fisher, Yael; Refael Fanyo, Ravit (Frontiers in Psychology, 2022)
This study aimed to examine how the level of communality (communal affiliation) affects parents' perception of children attending public elementary schools, the concept of teacher authority, and the concept of parental involvement. The study population consisted of 300 parents living in various parts of Israel who agreed to complete a self-reporting anonymous questionnaire. The questionnaire comprised three subsections: Scale of parents' perception of "parental involvement," which included 44 items, Cronbach's alpha value was .90.; The Scale of parents' perceptions of the concept of "Teacher's Authority," which included 25 items, Cronbach's alpha value was .79.; and one was composed primarily for the current study, the Scale of parents' perception of "Communality Level" which included 19 items, Cronbach's alpha value was .88. The findings were analyzed using structural equation models (SEM). Applying these measures to the current study rendered the following results: RMSEA = 0.007, TLI = 0.995, CFI = 0.99, NFI = 0.904, df = 16, χ² = 16.266, p = .435. Hence, the value of 1.01 (x^2/ⅆf ) < 3, the TLI and CFI > 0.95, The research findings indicated that a high level of communality (communal affiliation) among parents predicted high levels of perceived teachers' authority (β=.27) and parental involvement (β=.30). By contrast, it was also found that living in the same residential characteristics as the teachers predicted low levels of both perceived teacher authority (β=-.18) and parental involvement (β=-.20). As regards the theoretical aspects, it adds a new layer to educational research about the variables that affect perceptions of teacher authority, an issue that has received little attention in the research literature. In terms of its practical applications, the model can help education systems in general and schools, in particular, to formulate policies and take steps to improve the ever-important relationship between the school and the parents. Furthermore, the model clarifies our understanding of and ways to strengthen the teacher's authority.